Switching of Kinetically Relevant Reactants for the Aqueous Cathodic Process Determined by Mass‐transport Coupled with Protolysis. Issue 24 (5th November 2019) - Shinagawa, Tatsuya; Obata, Keisuke; Takanabe, Kazuhiro
Abstract: Electrocatalytic energy conversion driven by renewably generated electricity is a key technology to achieve a sustainable society in the future, namely, CO2 reduction and hydrogen production. Despite increasing research efforts dedicated to these reactions, there is no consensus regarding the proton source directly participating in surface reactions under non‐acidic pH conditions: Free proton (H + ) versus proton‐containing species (e. g., H2 O, Hx PO4 x−3, Hy CO3 y−2 ). We herein addressed this issue by rigorously quantifying the diffusion flux and protolysis rate during the aqueous hydrogen evolution reaction (HER). Our analysis revealed that there exists the linear free‐energy relationship (LFER) between the p K a and the rate of protolysis (HA→H + +A − ). Furthermore, the diffusion flux of the free proton as a consequence of the mass transport and protolysis failed to account for the typical current density of interest on the order of −10 mA cm −2 at non‐acidic pH levels when the K a value and the molarity of the buffering species were low; e. g., <−0.1 mA cm −2 was attainable at pH >5 in 1.0 M KHCO3 (p K a =10.3). As a result, under such circumstance, the proton‐containing species is suggested to directly react on the surface during the cathodic electrocatalytic reactions. Abstract : Free proton not favoured : Combined theoretical and experimental efforts answered the long‐standing question: "What is the kinetically relevant reactant for the hydrogen production in the non‐acidic aqueous phase?" – the proton‐containing species rather than the free proton, when appreciable current densities such as −10 mA cm −2 are reached.